Play in the Age of Goethe : Theories, Narratives, and Practices of Play around 1800 - Schreiber, Elliott, 1969-; Landgraf, Edgar, 1967- (Book collections on Project MUSE., 2020)
"We are inundated with game play today. Digital devices offer opportunities to play almost anywhere and anytime. No matter our age, gender, social, cultural, or educational background-we play. Play in the Age of Goethe: Theories, Narratives, and Practices of Play around 1800 is the first book-length work to explore how the modern discourse of play was first shaped during this pivotal period (approximately 1770-1830). The eleven chapters illuminate critical developments in the philosophy, pedagogy, psychology, politics, and poetics of play as evident in the work of major authors of the period including Lessing, Goethe, Kant, Schiller, Pestalozzi, Jacobi, Tieck, Jean Paul, Schleiermacher, and Fröbel. While drawing on more recent theories of play by thinkers such as Jean Piaget, Donald Winnicott, Jost Trier, Gregory Bateson, Jacques Derrida, Thomas Henricks, and Patrick Jagoda, the volume shows the debates around play in German letters of this period to be far richer and more complex than previously thought, as well as more relevant for our current engagement with play. Indeed, modern debates about what constitutes good rather than bad practices of play can be traced to these foundational discourses"--